Tröger’s Base-Derived Thermally Activated Delayed Fluorescence Dopant for Efficient Deep-Blue Organic Light-Emitting Diodes - Ze-Ling Wu; Xin Lv; Ling-Yi Meng; Xu-Lin Chen; Can-Zhong Lu (Molecules, 2023)
The development of efficient deep-blue emitters with thermally activated delayed fluorescence (TADF) properties is a highly significant but challenging task in the field of organic light-emitting diode (OLED) applications. Herein, we report the design and synthesis of two new 4,10-dimethyl-6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (TB)-derived TADF emitters, TB-BP-DMAC and TB-DMAC, which feature distinct benzophenone (BP)-derived acceptors but share the same dimethylacridin (DMAC) donors. Our comparative study reveals that the amide acceptor in TB-DMAC exhibits a significantly weaker electron-withdrawing ability in comparison to that of the typical benzophenone acceptor employed in TB-BP-DMAC. This disparity not only causes a noticeable blue shift in the emission from green to deep blue but also enhances the emission efficiency and the reverse intersystem crossing (RISC) process. As a result, TB-DMAC emits efficient deep-blue delay fluorescence with a photoluminescence quantum yield (PLQY) of 50.4% and a short lifetime of 2.28 μs in doped film. The doped and non-doped OLEDs based on TB-DMAC display efficient deep-blue electroluminescence with spectral peaks at 449 and 453 nm and maximum external quantum efficiencies (EQEs) of 6.1% and 5.7%, respectively. These findings indicate that substituted amide acceptors are a viable option for the design of high-performance deep-blue TADF materials.